The problematic restoration of a conceptual light artwork - Olivier Steib (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The "Erlauf" artwork by Jenny Holzer is a LED sign part of a series made in 1998,and was defective. A preliminary study was carried out before its restoration, which raised the difficulties relating to this kind of object. This case has allowed an international collaboration between the artist's studio, technicians, and museums, where the conservator-restorer is in charge of ethical and technical coordination and managing sometimes opposing points of view.